Critical perspectives on language teaching materials - Gray, John; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
This Critical Perspectives on Language Teaching Materials brings together a collection of critical voices on the subject of language teaching materials for use in English, French, Spanish, German and Content and Language Integrated Learning (CLIL) classrooms.
Keywords: Linguistics; Applied linguistics; Language and education; Teaching; Language and languages -- Study and teaching; Linguistics; Applied Linguistics; Teaching and Teacher Education; Language Education; Language Teaching